Molecular cloning and functional analysis of two calcium-associated cuticular protein genes in Neocaridina denticulata sinensis - Gao, Xi; Duan, Mengmeng; Sun, Yuying; Zhang, Jiquan (Journal of oceanology and limnology, 2024)
The body surface of crustaceans is covered with a sturdy shell. The growth and development of crustaceans are realized through molting. Neocaridina denticulata sinensis is a suitable candidate for crustacean scientific research. Two calcium-associated cuticular protein genes, named NdCAP-1 and NdCAP-2 , were obtained from N. denticulata sinensis . Molecular docking simulated the binding effect of both proteins and calcium ions. Semi-quantitative reverse transcription PCR results show that NdCAP-1 is expressed in D 2–4 stage, NdCAP-2 expressed in D 2–4 and A–B stages, and both were significantly expressed in the cephalothorax cuticle and pereiopods. Then, it was revealed that NdCAP-1 and NdCAP-2 are regulated by NdBcR -mediated 20E signaling pathways. Knockdown of NdCAP-1 and NdCAP-2 was observed to cause surface defects. The recombinant proteins (rNdCAP-1 and rNdCAP-2), obtained by prokaryotic expression, had calcium-binding and chitin-binding ability, inhibited formation of calcium carbonate precipitate. These results show that calcium-associated cuticular proteins play important roles in cuticle formation and calcification.